Margaret Laurence Critical Reflections - Staines, David (Reappraisals: Canadian Writers, 2001)
This book highlights the accomplishments of one of Canada's most acclaimed and beloved fiction writers, Margaret Laurence. The essays in this collection explore her body of work as well as her influence on young Canadian writers today.